Cultural Transfers (Not Only) at the Colonial Border of the New World - Křížová, Markéta (Dějiny – teorie – kritika, 2015)
The frontier regions of colonial empires offer themselves as almost ideal spaces for the study of two-way cultural transfers. The present article presents the possibilities, but also the limits of the study of cultural transfer and entangled history/histoire croisée on the example of the Jesuit missions on the borders of Spanish colonies in America, especially the northern frontier of the viceroyalty of New Spain (contemporary Mexico and Central America). Traditionally, historiography made use of the Jesuit texts more for illustrating the narratives of the advance of European colonization to the interior of the New World. But even though these testimonies are based on the European optic, they can be used also for the analysis of the view of the natives of the colonial processes and the role of the missionary as “knowledge brokers” on the level of material as well as spiritual culture. Important is the fact that the culture imprinted upon the natives was not homogeneous, as many of the missionaries in the peripheral regions were non-Spanish.